Trzynastka - Borzecka, Ewa (Poland : Telewizja Polska, 1997)
The film shows the every-day life of a poor female resident of a rural village in the Podkarpacie region, Poland, who raises thirteen children all by herself. It is a shocking, honest and painfully realistic portrait of a family in that region. The widow with thirteen children lives with cats, dogs, rabbits and rats in one room. The animals lose out in the fight for survival…
Keywords: Poland